Karp's cell biology - Iwasa, Janet; Marshall, Wallace F.; Karp, Gerald (John Wiley & Sons, 2018)
This classic text explores core concepts in considerable depth, often adding experimental detail. It is written in an inviting style to assist students in handling the plethora of details encountered in the Cell Biology course. In this edition, two new co-authors take the helm and help to expand upon the hallmark strengths of the book, improving the student learning experience.